The role of malate in plant homeostasis. - Finkemeier, I; Sweetlove, L (2009)
Malate is a central metabolite of the plant cell with important roles in plant physiology and metabolism. Here, we summarize the most recent advances in our understanding of malate homeostasis in central metabolism, guard cell functioning, and root exudation.